A Case of Intravascular Lymphoma with Increased Regional Cerebral Blood Flow in I-123 IMP Single-Photon Emission CT - Miyazaki, Chihoko (AJNR Am J Neuroradiol, 2004)
Summary: This report documents a case of intravascular lymphoma (IVL) with increased regional cerebral blood flow (rCBF) disclosed at I-123 IMP single-photon emission CT (IMP-SPECT). A 73-year-old woman with IVL had high rCBF disclosed by IMP-SPECT before chemotherapy; rCBF was normal after one course of CHOP (cyclophophamide, vincristine, doxorubicin, and prednisone) chemotherapy. During her clinical course, she had an episode in which she showed increased rCBF in the left cerebral hemisphere at IMP-SPECT performed immediately after the recovery from the right hemiparesis.